2004
DOI: 10.1152/ajprenal.00351.2002
|View full text |Cite
|
Sign up to set email alerts
|

ERK and p38 mediate high-glucose-induced hypertrophy and TGF-β expression in renal tubular cells

Abstract: We investigated the expression of ERK, p38 mitogen-activated protein kinase (p38), and JNK in renal tubules of diabetic rats following 3 wk after streptozotocin injection (DM). Although the expression of ERK was not different between controls and DM, phosphorylated ERK was expressed more intensely in DM. p38 And phosphorylated p38 were detected only in the diabetic kidney and were localized in all tubular segments. JNK and phosphorylated JNK were expressed similarly in controls and DM. Transforming growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
95
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 27 publications
12
95
0
1
Order By: Relevance
“…ERK activation is known to be involved in TGF-␤-induced collagen expression as well as HGinduced cellular hypertrophy in mesangial cells (59 -61). Blockage of ERK by specific ERK inhibitors has been shown to attenuate high glucose-induced cellular hypertrophy and fibronectin expression in mesangial cells and renal tubular cells (62,63), suggesting ERK as one of the signaling pathways in the progression of DN along with Akt (64). However, the molecular mechanisms by which TGF-␤ activates ERK are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…ERK activation is known to be involved in TGF-␤-induced collagen expression as well as HGinduced cellular hypertrophy in mesangial cells (59 -61). Blockage of ERK by specific ERK inhibitors has been shown to attenuate high glucose-induced cellular hypertrophy and fibronectin expression in mesangial cells and renal tubular cells (62,63), suggesting ERK as one of the signaling pathways in the progression of DN along with Akt (64). However, the molecular mechanisms by which TGF-␤ activates ERK are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney, ERK1/2 is expressed in all nephron segments and plays an important role in multiple physiological (33) and pathological processes (30). In contrast to other nephron segments, ERK1/2 appears to have basal activity in distal nephron cells (31,34), consistent with tonic inhibition of Na ϩ transport by the ERK pathway. It is well demonstrated that the components of the MAPK cascade (Raf-1, MEK1/2, and ERK1/2, in this case) exist in a multiprotein complex to permit the cell to perform coordinate regulation of several simultaneous possibly divergent signals at multiple levels (35).…”
Section: Gilz1 and Sgk1 Synergistically Stimulate Enac Cell Surface Ementioning
confidence: 95%
“…Prolonged exposure (1-13 d) of proximal tubular epithelial cells to hyperglycemic environment has been shown to inhibit cell proliferation and induce growth arrest or cellular MINIREVIEWS apoptosis [8][9][10][11][12] . These cellular effects are caused by the activation of a network of intracellular signaling pathways and include the phosphatidylinostiol 3 kinase (PI3 kinase)/adams kara taylor (AKT) signaling pathway [13] .…”
Section: Apoptosismentioning
confidence: 99%